Peran Departemen OHCD dalam Penguatan Ekosistem Pengembangan SDM melalui Program Pemagangan di PT PAL Indonesia - Evita Peron Silalahi; Sulastri Irbayuni (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
Abstact The internship program serves as a practical learning platform that enables students to gain real work experience within an industrial environment. PT PAL Indonesia, through the Organizational & Human Capital Development (OHCD) Department, implements a structured internship system covering administrative procedures, induction, placement, monitoring, and evaluation. This article examines the role of OHCD in strengthening the human resource development ecosystem through internship management. The findings indicate that OHCD functions not only as an administrative unit but also as a facilitator of learning, a mediator between departments, and an evaluator of student competencies. The internship contributes significantly to improving students’ work readiness through enhanced technical and soft skills, discipline, and an understanding of industrial work culture. However, its effectiveness is influenced by factors such as internship duration, student preparedness, and supervisory quality. Therefore, strengthening strategies such as monitoring digitalization, competency-based coaching, and curriculum alignment are required to ensure optimal implementation. The internship program has the potential to serve as a sustainable human resource development instrument when managed systematically and adaptively. Keywords: adaptation, internship, OHCD, work culture, human capital development